Kidney stone rarity in South Africa's black population : investigation of the biochemical and physico-chemical properties of Tamm Horsfall Mucoprotein as a possible contributory factor - Craig, Tracy-Ann (Department of Chemistry, 2014)
Includes bibliographical references.